Altitude training in endurance running: perceptions of elite athletes and support staff. Issue 2 (17th January 2019) - Turner, Gareth; Fudge, Barry W; Pringle, Jamie S M; Maxwell, Neil S; Richardson, Alan J
ABSTRACT: This study sought to establish perceptions of elite endurance athletes on the role and worth of altitude training. Elite British endurance runners were surveyed to identify the altitude and hypoxic training methods utilised, along with reasons for use, and any situational, cultural and behaviour factors influencing these. Prior to the 2012 Olympics Games, 39 athletes and 20 support staff (coaches/practitioners) completed an internet-based survey to establish differences between current practices and the accepted "best-practice". Almost all of the athletes (98%) and support staff (95%) surveyed had utilised altitude and hypoxic training, or had advised it to athletes. 75% of athletes believed altitude and hypoxia to be a "very important" factor in their training regime, with 50% of support staff believing the same. Athletes and support staff were in agreement of the methods of altitude training utilised (i.e. 'hypoxic dose' and strategy), with camps lasting 3–4 weeks at 1, 500–2, 500 m being the most popular. Athletes and support staff are utilising altitude and hypoxic training methods in a manner agreeing with research-based suggestions. The survey identified a number of specific challenges and priorities, which could provide scope to optimise future altitude training methods for endurance performance in these elite groups.